Does Body Shape in Fundulus Adapt to Variation in Habitat Salinity? - Styga, Joseph M.; Pienaar, Jason; Scott, Peter A.; Earley, Ryan L. (Frontiers in Physiology, 2019)
Understanding the ecological pressures that generate variation in body shape is important because body shape profoundly affects physiology and overall fitness. Using Fundulus, a genus of fish that exhibits considerable morphological and physiological variation with evidence of repeated transitions between freshwater and saltwater habitats, we tested whether habitat salinity has influenced the macroevolution of body shape at different stages in development. After accounting for phylogenetic inertia, we find that body shape deviates from the optimal streamlined shape in a manner consistent with different osmoregulatory pressures exerted by different salinity niches at every stage of ontogeny that we examined. We attribute variation in body shape to differential selection for osmoregulatory efficiency because: 1) saline intolerant species developed body shapes with relatively low surface areas more conducive to managing osmoregulatory demands and, 2) inland species that exhibit high salinity tolerances have body shapes similar to saline tolerant species in marine environments.